McGRATH MAC videolaryngoscope versus Macintosh laryngoscope for orotracheal intubation in intensive care patients: the randomised multicentre MACMAN trial study protocol. Issue 12 (23rd December 2015) - Bailly, Arthur; Lascarrou, Jean Baptiste; Le Thuaut, Aurelie; Boisrame-Helms, Julie; Kamel, Toufik; Mercier, Emmanuelle; Ricard, Jean Damien; Lemiale, Virginie; Champigneulle, Benoit; Reignier, Jean
Abstract : Introduction: Critically ill patients with acute respiratory, neurological or cardiovascular failure requiring invasive mechanical ventilation are at high risk of difficult intubation and have organ dysfunctions associated with complications of intubation and anaesthesia such as hypotension and hypoxaemia. The complication rate increases with the number of intubation attempts. Videolaryngoscopy improves elective endotracheal intubation. McGRATH MAC is the lightest videolaryngoscope and the most similar to the Macintosh laryngoscope. The primary goal of this trial was to determine whether videolaryngoscopy increased the frequency of successful first-pass intubation in critically ill patients, compared to direct view Macintosh laryngoscopy. Methods and analysis: MACMAN is a multicentre, open-label, randomised controlled superiority trial. Consecutive patients requiring intubation are randomly allocated to either the McGRATH MAC videolaryngoscope or the Macintosh laryngoscope, with stratification by centre and operator experience. The expected frequency of successful first-pass intubation is 65% in the Macintosh group and 80% in the videolaryngoscope group. With α set at 5%, to achieve 90% power for detecting this difference, 185 patients are needed in each group (370 in all). The primary outcome is the proportion of patients with successful first-pass orotracheal intubation, compared between the two groups using a generalised mixed model to take the stratification factors into account. Ethics and dissemination: The study project has been approved by the appropriate ethics committee (CPP Ouest 2, # 2014-A00674-43). Informed consent is not required, as both laryngoscopy methods are considered standard care in France; information is provided before study inclusion. If videolaryngoscopy proves superior to Macintosh laryngoscopy, its use will become standard practice, thereby decreasing first-pass intubation failure rates and, potentially, the frequency of intubation-related complications. Thus, patient safety should benefit. Further studies would be warranted to determine whether videolaryngoscopy is also beneficial in the emergency room and for prehospital emergency care. Trial registration number: NCT02413723; Pre-results.